A new silica-infiltrated Y-TZP obtained by the sol-gel method - Campos, T. M.B.; Ramos, N. C. [UNESP]; MacHado, J. P.B.; Bottino, M. A. [UNESP]; Souza, R. O.A.; Melo, R. M. [UNESP] (Elsevier, 2016)
Objective The aim of this study was to evaluate silica infiltration into dental zirconia (VITA In-Ceram 2000 YZ, Vita Zahnfabrik) and its effects on zirconia's surface characteristics, structural homogeneity and bonding to a resin cement. Methods Infiltration was performed by immersion of the pre-sintered zirconia specimens in silica sols for five days (ZIn). Negative (pure zirconia specimens, ZCon-) and positive controls (specimens kept in water for 5 days, ZCon+) were also performed. After sintering, the groups were evaluated by X-ray diffraction (XRD), grazing angle X-ray diffraction (DRXR), scanning electron microscopy (SEM), contact angle measurements, optical profilometry, biaxial flexural test and shear bonding test. Weibull analysis was used to determine the Weibull modulus (m) and characteristic strength (σ0) of all groups. Results There were no major changes in strength for the infiltrated group, and homogeneity (m) was also increased. A layer of ZrSiO4 was formed on the surface. The bond strength to resin cement was improved after zirconia infiltration, acid conditioning and the use of an MDP primer. Conclusion The sol-gel method is an efficient and simple method to increase the homogeneity of zirconia. Infiltration also improved bonding to resin cement. Clinical significance The performance of a zirconia infiltrated by silica gel improved in at least two ways: structural homogeneity and bonding to resin cement. The infiltration is simple to perform and can be easily managed in a prosthesis laboratory.
Keywords: Bond strength; Flexural strength; Silica; Sol-gel; Weibull; Zirconia